Comparing the recovery characteristics between sevoflurane and isoflurane following removal of laryngeal mask airway under deeper planes of anesthesia in pediatric surgical patients: An observational study - Nidha Rasool; Raja Suhail Shounthoo; Pareesa Rashid; Basharat Farooq (Asian Journal of Medical Sciences, 2025)
Background: Respiratory complications during emergence from general anesthesia present serious concerns in pediatric patients. Deep extubation excludes airway stimulation under lighter planes of anesthesia, but renders the patient with an unprotected airway susceptible to aspiration and obstruction. It is therefore desirable to prefer an anesthetic technique that would reduce the time interval between removal of airway device and patient awakening. Aims and Objectives: The aim of this study was to compare the effects of isoflurane and sevoflurane on emergence characteristics under deeper planes of anesthesia in pediatric surgical patients. Materials and Methods: Ninety-two pediatric patients stationed for lower abdominal surgeries were assigned into Group I, 45 patients (isoflurane) and Group II, 47 patients (sevoflurane). The patients were observed during recovery from anesthesia and various parameters recorded. Results: Patients in Group II attained spontaneous movement earlier than Group I; (6.33±1.45 min vs. 9.01±1.37 min [P<0.05]), timing of shifting from the operating room to recovery and spontaneous eye opening was significantly shorter in Group II than in Group I; (8.63±1.51 min vs. 11.76±1.22 min [P<0.05]) and (10.25±1.52 min vs. 13.29±1.22 min [P<0.05]), respectively. However, the actual discharge readiness and time of shifting from recovery room was similar for both Group I and Group II [35.35±2.50 min vs. 34.46±2.41 min [P>0.05]). Conclusion: Laryngeal mask airway removal under deep sevoflurane anesthesia leads to early attainment of an arousable state and return of protective airway reflexes.